Perspectives, understandings of dementia and lived experiences from Australian Aboriginal people in Western Australia. (20th February 2022) - Gubhaju, Lina; Turner, Kyle; Chenhall, Richard; Penny, Elsie; Drmota, Susan; Hawea, Shanelle; Carroll, Sophie‐Lee; Hunt, Kerry; Eades, Francine; Eades, Sandra
Abstract: Objective: We explored understandings about dementia and lived experiences from carers among community‐dwelling Aboriginal people in Western Australia (WA). Methods: In partnership with Aboriginal medical services in WA, we conducted semi‐structured interviews with Aboriginal people in Perth and Bunbury. All interviews were transcribed verbatim and coded thematically. Results: We conducted 39 interviews. Dementia was associated with ' losing your memory', a ' change in behaviour ' and unhealthy lifestyles. Increasing awareness about dementia in the community was noted particularly to enable people to recognise the early signs, feel safe to ask for help and know how to best support families. Families were primarily responsible for caring for people with dementia and were finding it difficult to manage. They expressed negative experiences with currently available aged care facilities. Conclusions: Increased awareness of dementia in the community through public health messaging and by health professionals and culturally secure services focussing on dementia care is required.